Into unknown skies : an unlikely team, a daring race, and the first flight around the world - Randall, David K. (Mariner Books, 2024)
"Equal parts THE RIGHT STUFF and THE BOYS IN THE BOAT, INTO UNKNOWN SKIES tells the unbelievable history of the 1924 race to circumnavigate the globe for the first time by air, a nail-biting contest that pitted underdog US pilots against their better-funded European rivals, created technology that changed aviation, and convinced America that its future was in the sky. In the early 1920s, America's faith in aviation was in shambles. Twenty years after the Wright Brothers' first flight, most Americans believed airplanes were for delivering the mail or performing daredevil stunts in front of crowds. The dream of commercial air travel remained just that. Even the American military was a skeptic-rather than pay to bring its planes back from Europe following World War I, the War Department chose to burn most of them instead. All that changed with a single race in 1924. It was not just any race, though-it was a race to become the first to circle the globe in an airplane, pitting a team of four underdog American pilots against the best aviators in the world from England, Italy, Portugal, France, and Argentina. Rooted in the same daring spirit that pushed early twentieth-century explorers to attempt crossings of the Antarctic ice or locate the source of the Nile, this race was an adventure unlike anything the world had seen before. The obstacles were daunting-from experimental planes, to dangerous landings in uncharted territory, to the simple navigational gauges that could lead pilots hundreds of miles off course. Failure seemed all but guaranteed-the suspense less about who would win than how many would perish for the honor of being the first. Now on the race's centennial, award-winning author David K. Randall tells the story of this riveting, long-forgotten race. Through larger-than-life characters, treacherous landings, disease, and ultimately triumph, INTO UNKNOWN SKIES demonstrates how one race returned America to aviation greatness. A story of underdog teammates, bold exploration, and American ingenuity, INTO UNKNOWN SKIES is an untold adventure tale showing the power of flight to bring the world together"--